(untitled) (Communications in Computational Physics, 2008)
The steady-state heat conduction in heat conductors with temperature dependent thermal conductivity and mixed boundary conditions involving radiation is investigated using the method of fundamental solutions. Various computational issues related to the method are addressed and numerical results are presented and discussed for problems in two and three dimensions.